New approaches to problem-based learning revitalising your practice in higher education - Barrett, Terry; Moore, Sarah (Routledge, 2011)
Problem-based learning (PBL) is a pedagogical approach that has the capacity to create vibrant and active learning environments in higher education. However, both experienced PBL practitioners and those new to PBL often find themselves looking for guidance on how to engage and energise a PBL curriculum.